População LGBTI+ e política de assistência social: Proteção ou desproteção social? - Hanashiro, Mariko (2024)
The theme of this research is care for the LGBTI+ population in social assistance policy, seeking to study how social assistance policy has been implemented as part of the protective system for this public. Its object is the Mediations of the Social Assistance Policy in the care of the LGBTI+ population and the guarantee of social protection and security. Its general aim is to study how the social assistance policy has been implemented as part of the protection system for the LGBTI+ population and how this policy has been recognized and legitimized as a guarantor of social protection for this group. In terms of methodology, the work was based on the ontological foundations of historical-dialectical materialist thinking. To this end, bibliographical and documentary research was used, as well as empirical research through interviews. Ten interviews were conducted with various actors in the social assistance policy: users, workers, social assistance policy managers and social movements/activists. The main regulations on the LGBTI+ population and social assistance policy are the mention of this group in the Second Ten-Year Plan and Joint Resolution CNAS and CNCD/LGBT No. 01/2018. Thus, from the studies it was possible to conclude that it is not possible to say that the social assistance policy does not serve the LGBTI+ population, but that it serves this public in reduced volume, with bottlenecks between demand (raised from social movements, studies and data from Dial 100) and real access to services, programs and benefits. There are still no records of LGBTI+ workers in social assistance policy. It was unanimous in the interviews, however, that the impact of the work of professionals in SUAS is ultimately the subject that will or will not guarantee social protection and the rights of its users, altering the experiences of the people served and the experiences provided to them. The interviewees had a wide range of experiences in relation to this social policy, including situations of social protection and experiences of violence and rights violations. At the end of the dissertation, it was possible to identify some bottlenecks and proposals aimed at guaranteeing social protection in the social assistance policy for the LGBTI+ population